2021
DOI: 10.7150/jca.58049
|View full text |Cite
|
Sign up to set email alerts
|

ADNP prompts the cisplatin-resistance of bladder cancer via TGF-β-mediated epithelial-mesenchymal transition (EMT) pathway

Abstract: Activity-dependent neuroprotective protein (ADNP) is vital for embryonic development and brain formation. Besides, the upregulated expression of ADNP enhances tumorigenesis in some human tumors like bladder cancer (BC). However, the potential roles of ADNP in drug resistance and the related mechanisms in BC is unknown. We performed this study to elucidate the influence of ADNP in the chemoresistance of BC and tried to explore the underlying molecular mechanism. The expressions of ADNP in BC from progression an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 44 publications
1
9
0
Order By: Relevance
“…Activity-dependent neuroprotector homeobox (ADNP), a transcription factor and cytoskeletal-binding protein, plays a crucial role in cellular growth and proliferation. 38 Wound healing experiments have shown that ADNP promotes cell migration. 39 NAP, a brief peptide with eight amino acids derived from ADNP, acts as a protective agent against cerebral ischaemia, central nervous system complications of DM, and retinal damage induced by different insults.…”
Section: Discussionmentioning
confidence: 99%
“…Activity-dependent neuroprotector homeobox (ADNP), a transcription factor and cytoskeletal-binding protein, plays a crucial role in cellular growth and proliferation. 38 Wound healing experiments have shown that ADNP promotes cell migration. 39 NAP, a brief peptide with eight amino acids derived from ADNP, acts as a protective agent against cerebral ischaemia, central nervous system complications of DM, and retinal damage induced by different insults.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, there is increasing consensus that ADNP contributes to tumorigenesis and cancer progression. Transcriptional assessment of ADNP levels in a large cohort of bladder cancer specimens highlighted a significant overexpression in the patients with tumor progression and the association of higher ADNP protein levels to poor prognosis in such patients [ 161 ]. In bladder cancer, ADNP promotes tumor cell growth and proliferation by enhancing the AKT-MDM2-p53 molecular axis which stabilizes cyclin D1 and ultimately leads to cell cycle acceleration from G1 phase to S phase [ 162 ].…”
Section: Adnp Dysregulation In Cancer Developmentmentioning
confidence: 99%
“…In bladder cancer, ADNP promotes tumor cell growth and proliferation by enhancing the AKT-MDM2-p53 molecular axis which stabilizes cyclin D1 and ultimately leads to cell cycle acceleration from G1 phase to S phase [ 162 ]. In another study, ADNP was found to promote bladder cancer cell migration via TGF- β -mediated epithelial-mesenchymal transition (EMT) pathway [ 161 ]. In that respect, it is relevant to mention that ADNP was recently identified as a binding partner of the ZEB1/NuRD complex (zinc finger E-box-binding homeobox 1/Nucleosome Remodeling and Deacetylase) which is critically involved in epigenetic cancer programming of EMT hallmarks [ 163 ].…”
Section: Adnp Dysregulation In Cancer Developmentmentioning
confidence: 99%
“…In addition to recurrence, EMT is also involved in mediating chemoresistance; in fact, EMT, recurrence, and chemoresistance work in concert with one another. Studies have found that EMT markers are upregulated in chemoresistant cells, with restoration of sensitivity via TGF-beta downregulation [ 75 ] and that oncogenic proteins modulate EMT to induce resistance to chemotherapeutic agents [ 76 , 77 ]. Two key pathways that have been linked to the EMT phenotype are Wnt signaling [ 78 , 79 ] and TGF-beta [ 80 , 81 ].…”
Section: Emtmentioning
confidence: 99%